Multiple opportunistic infection-associated hemophagocytic lymphohistiocytosis in nephrotic syndrome: A case report - Sireesh Varadaraju; Priyanka Khandelwal; Jhuma Sankar; Pankaj Hari (Wolters Kluwer Medknow Publications, 2021)
Multiple opportunistic coinfections during corticosteroid therapy for the nephrotic syndrome are uncommon. Infection-associated hemophagocytic lymphohistiocytosis (HLH) is a rare and potentially fatal multisystem disorder, manifesting as a state of hypercytokinemia in response to an infectious trigger. We describe a 4½-year-old boy with steroid-dependent nephrotic syndrome receiving high-dose steroids, who developed respiratory failure due to pulmonary tuberculosis, Cytomegalovirus, and Pneumocystis jirovecii coinfections; HLH complicated the course. Aggressive management of the underlying infections with antitubercular, antiviral, and antifungal therapy, prompt recognition of HLH, and immunomodulation with intravenous (IV) immunoglobulin and IV methylprednisolone enabled convalescence. This report emphasizes the serious risks of immunosuppression and the need for strict vigilance for rare opportunistic infections with multiple pathogens in patients receiving oral steroids for nephrotic syndrome. Clinical distinctions between severe sepsis and HLH may be ambiguous; a high level of suspicion is required for timely recognition and management.